Nonlinear finite element modeling of rectangular/square concrete columns confined with FRP - Doran, B.; Koksal, H. O.; Turgay, T. (ELSEVIER SCI LTD, 2009)
Numerous confinement models which can be categorized as design or analysis oriented have been proposed for predicting the behavior of fiber-reinforced polymer (FRP)-confined concrete columns. Analysis-oriented models generally use an incremental procedure for plotting the entire stress-strain response while design-oriented models predict the load-carrying and deformation capacities of the column with closed form expressions. As a comprehensive approach, this paper primarily deals with the nonlinear finite element modeling of rectangular/square concrete columns wrapped with FRP in order to simulate the compressive behavior under concentric loading. Adopting cohesion and internal friction values of Drucker-Prager criterion from a previous study of the authors, emphasis is placed on both the determination of confining stress and the lateral-to-axial strain relation. Thirty three small and large scale specimens. including slender columns, tested by four different researchers are numerically analyzed for this crucial relation between the behavior of concrete and composite jacket. The distribution of confining stresses at the mid-height plane of the columns is evaluated on the basis of analysis. Confining stresses obtained from nonlinear finite element analyses (NLFEA) are also compared with both uniform confining pressure for cylindrical specimens and effective stresses calculated by using a shape factor recommended by ACI 440.2R-02. Comparisons show that the confining pressure values obtained from the assumption of uniform stress distribution over the surface of concrete core are consistent with the maximum lateral pressure at the corners while effective lateral pressure can be considered as minimum confining stresses on flat sides. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Concrete; Column; Drucker-Prager criterion; Finite element analysis; Fiber reinforced polymer; Confinement; Shape factor; STRESS-STRAIN MODEL; Materials Science